2000
DOI: 10.1097/00062752-200011000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood transplants

Abstract: With the establishment of cord blood banks, the number of related and unrelated umbilical cord blood transplants is increasing worldwide. Close links have been established with the cord blood banks. Available data showed that umbilical cord blood transplants offer overall results comparable to those obtained with related or unrelated bone marrow transplants. Several differences were found: engraftment with cord blood was delayed, resulting in an increased incidence of early transplant complications, and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…[8][9][10][11][12][13][14] with hematological disorders were enrolled in this study and received co-transplantation of UCB cells and parental-derived MSCs between May 2006 and January 2008. The results of these 13 patients were compared with those obtained in a group of 39 historical controls (median age 4 years, range 0.…”
Section: Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10][11][12][13][14] with hematological disorders were enrolled in this study and received co-transplantation of UCB cells and parental-derived MSCs between May 2006 and January 2008. The results of these 13 patients were compared with those obtained in a group of 39 historical controls (median age 4 years, range 0.…”
Section: Patientsmentioning
confidence: 99%
“…The results of these 13 patients were compared with those obtained in a group of 39 historical controls (median age 4 years, range 0. [8][9][10][11][12][13][14][15][16][17] transplanted in one of the three centers (Pavia, Leiden and Stockholm) and matched as closely as possible for original disease and type of UCB donor used. Details on the study population and controls are reported in Table 1.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,11 The majority of reports of UCBT are from cord blood bank registries or cord blood banks. 5,12,13 However, in a large single center experience at the University of Minnesota, Wagner et al reported results of transplantation of unrelated donor umbilical cord blood in 102 patients with malignant and nonmalignant diseases. 2 The main objective of this study is to report the outcomes, namely, hematological recovery, GVHD, transplantation-related mortality and overall survival (OS) of unrelated cord blood transplants in children performed in one center over the last 5 years.…”
mentioning
confidence: 99%